2021
DOI: 10.1093/plcell/koab046
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Splicing Variant of PtRD26 Delays Leaf Senescence by Regulating Multiple NAC Transcription Factors in Populus

Abstract: During leaf senescence, the final stage of leaf development, nutrients are recycled from leaves to other organs, and therefore proper control of senescence is thus critical for plant fitness. Although substantial progress has been achieved in understanding leaf senescence in annual plants, the molecular factors that control leaf senescence in perennial woody plants are largely unknown. Using RNA sequencing, we obtained a high-resolution temporal profile of gene expression during autumn leaf senescence in popla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 88 publications
1
71
0
Order By: Relevance
“…The specific primers were designed by Primer Premier 6.0 and examined by NCBI Primer-BLAST (https://www.ncbi.nlm.nih.gov/ tools/primerblast/, accessed on 15 July 2021) (Supplementary Table S4). The selection of reference genes of P. euphratica was based on the research of Wang et al [80,81]. Real-time PCR was run with the CFX96 Touch™ instrument (Bio-Rad, Hercules, CA, USA) to detect the chemical SYBR Green.…”
Section: Rna Extraction Cdna Synthesis and Qrt-pcr Analysismentioning
confidence: 99%
“…The specific primers were designed by Primer Premier 6.0 and examined by NCBI Primer-BLAST (https://www.ncbi.nlm.nih.gov/ tools/primerblast/, accessed on 15 July 2021) (Supplementary Table S4). The selection of reference genes of P. euphratica was based on the research of Wang et al [80,81]. Real-time PCR was run with the CFX96 Touch™ instrument (Bio-Rad, Hercules, CA, USA) to detect the chemical SYBR Green.…”
Section: Rna Extraction Cdna Synthesis and Qrt-pcr Analysismentioning
confidence: 99%
“…Owing to their crucial function in the formation of the embryos and flowers of petunias, NAC TFs were widely studied, and multiple reports identified its key role in plant growth and development [12,13]. A large number of NAC-encoding genes have been identified and confirmed in various plants for their role in regulating wood formation [14], leaf senescence [15], fruit development [16,17], and flower morphogenesis [18,19]. Furthermore, NAC TFs also are involved in various biotic and abiotic stress responses in many plants such as Populus tomentosa [20], Arabidopsis thaliana [21], Oryza sativa [22,23], Glycine max [24], Arachis hypogaea [25], and Xanthoceras sorbifolia [26].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that TF plays a key regulatory role in leaf senescence, however, most of the studies have mainly focused on a few families, including the NAC or WRKY families, and more studies are needed in the future to analyze whether other family TFs are also involved in leaf senescence. A recent transcriptomic study revealed that 115 Sen-TFs from 31 families are involved in autumn leaf senescence in poplar ( Wang et al, 2021 ), further supporting this suggestion.…”
Section: Multiple-layers Of Regulation On Leaf Senescencementioning
confidence: 62%